2022
DOI: 10.1021/acsanm.2c02852
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cu2+-Doped Ca2SiO4 Nanosphere for Cancer Therapy via Double Ion Interference

Abstract: Ion interference therapy (IIT) is a promising cancer treatment strategy that can reverse ion distribution via bioactive nanomaterials so as to interfere with or hinder the physiological processes such as metabolism and proliferation of tumor cells. In this study, a dendritic Cu 2+ -doped calcium silicate nanosphere (Ca 2 SiO 4 ) loaded with ruthenium red (RuR) and disulfiram (DSF) (RD-CCP) was constructed for self-enhanced chemodynamic therapy and IIT of tumors through the combination of Cu and Ca. Under the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In addition, X-ray also causes calcium overload, which is also a factor contributing to irreversible cell damage. 50 By Fluo-4 probe staining, we found that the relative fluorescence intensity of calcium in the Ta@ PVP NPs + X-ray + NIR group was significantly stronger than that of the X-ray group (Figures 4d and S8c). The above experiments indicated that Ta@PVP NPs effectively enhanced X-ray-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, X-ray also causes calcium overload, which is also a factor contributing to irreversible cell damage. 50 By Fluo-4 probe staining, we found that the relative fluorescence intensity of calcium in the Ta@ PVP NPs + X-ray + NIR group was significantly stronger than that of the X-ray group (Figures 4d and S8c). The above experiments indicated that Ta@PVP NPs effectively enhanced X-ray-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure c,g, the Ta@PVP NPs + X-ray + NIR group had a significant MMP change under the indication of the JC-1 probe and caspase 3 activity enhancement. In addition, X-ray also causes calcium overload, which is also a factor contributing to irreversible cell damage . By Fluo-4 probe staining, we found that the relative fluorescence intensity of calcium in the Ta@PVP NPs + X-ray + NIR group was significantly stronger than that of the X-ray group (Figures d and S8c).…”
Section: Resultsmentioning
confidence: 94%
“…As such, understanding intracellular calcium ion homeostasis has become a focal point of antitumor research. [83,84] Disruption of intracellular calcium homeostasis can lead to severe oxidative stress, resulting in cell necrosis, apoptosis, or autophagy-mediated cell death. Therefore, the accumulation of free Ca 2+ in cells represents a critical point of concern, as it can result in calcium overload and the subsequent injury or death of various cell types.…”
Section: Iitmentioning
confidence: 99%
“…(3) The released Cu 2+ will be reduced by intracellular glutathione (GSH) to generate Fenton agent Cu + , which can catalyze the self-supplied H 2 O 2 and intrinsic intracellular H 2 O 2 to produce toxic hydroxyl radical by a Cu + -mediated Fenton-like reaction for inducing cell apoptosis. Although previous researches reported the multifunctional nanoplatform with Ca 2+ and Cu 2+ ions, both of them focused on the generation of toxic hydroxyl radical for inducing cancer cell apoptosis. This study provides innovative ideas for designing Ca 2+ /Cu 2+ dual-ion-based inorganic NPs-induced microenvironmental responsive “ion interference” multimodal nanotherapy platform for inducing paraptosis together with apoptosis and also insight for comprehensive treatment of cancer treatment for better therapeutic effect by apoptosis evasion.…”
Section: Introductionmentioning
confidence: 99%